2016
DOI: 10.1016/j.exphem.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

PARP-inhibitor-induced synthetic lethality for acute myeloid leukemia treatment

Abstract: Please cite this article as: Zhao L, Eric So CW, PARPi-induced synthetic lethality for acute myeloid leukaemia treatment, Experimental Hematology (2016), doi: 10.1016/j.exphem.2016.07.007. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…The inhibition of PARP1 induces the formation of SSBs, which then evolve into DSBs that in normal cells are repaired by the HR [45]. However, in cells where the HR is defective, such as those with mutated BRCA1 or BRCA2, PARP1 inhibition induces an excessive accumulation of genotoxic damage which triggers cell death, and this synthetic lethality effect has been effectively exploited in the treatment of Brca1-defective solid tumors [46]. More recent studies have shown that PARP1 inhibitors may also find application for the treatment of certain hematological malignancies.…”
Section: The Essential Function Of Ddr In the Maintenance Of Hscsmentioning
confidence: 99%
“…The inhibition of PARP1 induces the formation of SSBs, which then evolve into DSBs that in normal cells are repaired by the HR [45]. However, in cells where the HR is defective, such as those with mutated BRCA1 or BRCA2, PARP1 inhibition induces an excessive accumulation of genotoxic damage which triggers cell death, and this synthetic lethality effect has been effectively exploited in the treatment of Brca1-defective solid tumors [46]. More recent studies have shown that PARP1 inhibitors may also find application for the treatment of certain hematological malignancies.…”
Section: The Essential Function Of Ddr In the Maintenance Of Hscsmentioning
confidence: 99%
“…While one defect is not generally detrimental to a cells survival, the synthetic introduction of another pathway defect can be enough to push a cell into such disarray that the only option it faces is apoptosis [23].…”
Section: Non-homologous End Joiningmentioning
confidence: 99%
“…Acute myeloid leukaemia (AML) is a malignant disorder characterised by the accumulation of genetic aberrations in the myeloid haematopoiesis linage, that can be risk classified according to specific gene mutations (1). Understanding the AML genome promises new therapeutic strategies that involve synthetic lethal interactions (2). Thus, in this study we compare the effects of combining olaparib, a poly (ADP-ribose) polymerase (PARP) inhibitor that induces synthetic lethality in malignancies bearing homologous recombination deficiencies (2) and daunorubicin (ODC) with the standard daunorubicin-cytarabine (CDR) that models the "7+3" induction regimens.…”
mentioning
confidence: 99%
“…Understanding the AML genome promises new therapeutic strategies that involve synthetic lethal interactions (2). Thus, in this study we compare the effects of combining olaparib, a poly (ADP-ribose) polymerase (PARP) inhibitor that induces synthetic lethality in malignancies bearing homologous recombination deficiencies (2) and daunorubicin (ODC) with the standard daunorubicin-cytarabine (CDR) that models the "7+3" induction regimens. Two AML cell lines were chosen: OCI/AML3 and THP-1.…”
mentioning
confidence: 99%
See 1 more Smart Citation